Synthesis of the C6–C14 Fragment of Euphosalicin - Aichinger, Christian; Mulzer, Johann; Rinner, Uwe (Synlett, 2015)
The synthesis of the C6–C14 fragment of euphosalicin, a highly oxygenated modified jatrophane diterpene, is described. Key steps in the preparation of this versatile intermediate are an Ireland–Claisen rearrangement and a Shibasaki direct asymmetric aldol reaction.
Keywords: natural products; total synthesis; aldol reaction; rearrangement; hydrostannation